Control strategy of Grid-Connected PV Inverters in Microgrid with Nonlinear Operating Conditions - Naderipour A.; Abdul-Malek Z.; Abohamzeh E.; Ramachandaramurthy V.K.; Miveh M.R. (Institute of Electrical and Electronics Engineers Inc., 2023)
Electric current control; Electric inverters; MATLAB; Current control strategy; Grid connected inverters; Grid-connected PV inverters; Harmonics; Micro grid; Photovoltaic; Three-phase three-wire; Total harmonic distortion (THD); Harmonic analysis